La loucherie au pouvoir - Paul Cournarie (Cahiers Mondes Anciens)
Hellenistic kings were polygamous and then monogamous, transgressing social norms, then abiding by them. This paper aims to show that this transgression is best explained politically. King’s initial situation is representative of all power structure, but its peculiar salience depends on the Diadochs’ special situation: setting up a new authority, leaning on the extraordinary characteristics of one man. Paradoxically, their normalization is tied to an innovation: the women’s changing role at the head of the state.